Predictors and Association With Clinical Outcomes of the Changes in Exercise Capacity After Transcatheter Aortic Valve Replacement. Issue 7 (15th August 2017) - Abdul-Jawad Altisent, Omar; Puri, Rishi; Regueiro, Ander; Chamandi, Chekrallah; Rodriguez-Gabella, Tania; del Trigo, Maria; Campelo-Parada, Francisco; Couture, Thomas; Marsal, Josep Ramon; Côté, Mélanie; Paradis, Jean-Michel; DeLarochellière, Robert; et al.
Abstract : Background: At present, there are no objective data specifically examining the clinical impact of variations in exercise capacity post–transcatheter aortic valve replacement (TAVR). We describe the changes in exercise capacity between baseline and 6 months post-TAVR, and ascertain factors associated with and clinical implications of a lack of improvement in exercise capacity post-TAVR. Methods: A total of 305 patients (mean age, 79±9 years; 44% men; Society of Thoracic Surgeons predicted risk mortality score, 6.7±4.2%) undergoing TAVR completed both baseline and follow-up exercise capacity assessments at 6 months post-TAVR. Exercise capacity was evaluated by the 6-minute walk test (6MWT). Clinical outcomes were compared between patients displaying greater than (n=152; improving group) versus less than (n=153; nonimproving group) the median percentage change in distance walked between baseline and 6-month follow-up examinations. The primary outcome measure was clinical event rates, measured from the 6-month post-TAVR period onward. Further dichotomization according to baseline 6MWT distance (less than versus more than median walking distance, or slow walker versus fast walker) was also assessed. Results: The mean overall distances walked pre- and post-TAVR (6 months post-TAVR) were 204±119 and 263±116 m, respectively (Δ6MWT=60±106 m), with 219 (72%) patients demonstrating an increase in their walking distance (median percentage increase of the entire population was 20% [interquartile range, 0%–80%]). Factors independently correlated with reduced exercise capacity improvement included a range of baseline clinical characteristics (older age, female sex, chronic obstructive pulmonary disease; P <0.05 for all), periprocedural major or life-threatening bleeding ( P =0.009) and new-onset anemia at 6 months post-TAVR ( P =0.009). Failure to improve the 6MWT distance by at least 20% was independently associated with all-cause mortality ( P =0.002) and cardiovascular death or rehospitalization for cardiovascular causes ( P =0.001). Baseline slow walkers who were able to improve the 6MWT distance presented with significantly better outcomes than nonimprovers ( P =0.01 for all-cause mortality; P =0.001 for cardiovascular end point). Conclusions: Approximately one-third of patients undergoing TAVR did not improve their exercise capacity postprocedure. The lack of functional improvement post-TAVR was predicted by a mix of baseline and periprocedural factors translating into poorer clinical outcomes. These results suggest that systematically implementing exercise capacity assessment pre- and post-TAVR may help to improve patient risk stratification. Abstract : Supplemental Digital Content is available in the text.